Current evidence shows no reduction in mortality or re-infarction rate with early mobilisation following myocardial infarction. Issue 2 (1st May 2010) - Noureddine, Samar
Abstract : Commentary on: Cortes OL Villar JC Devereaux PJ . Early mobilisation for patients following acute myocardiac infarction: a systematic review and meta-analysis of experimental studies . Int J Nurs Stud 2009 ;46 :1496 –504 .